Treatment of hip luxation in dogs using bone screws and acrylic external fixator - Canpolat, I; Gunay, C (Indian Veterinary Journal, 2004)
Many methods have been described to treat hip luxation in dogs. Extra-articular methods for stabilisation of the joint have been described, including repair of the joint capsule (Allen and Chambers, 1986), transposition of the greater trochanter (Denny and Butterworth, 2000), insertion of a DeVita pin (Leeds and Renegar, 1979), and flexible external fixation for craniodorsal coxofemoral luxation (McLaughlin and Tillson 1994). This paper discribes a surgical technique for treatment of hip luxation in dogs using bone screws and acrylic external fixator.
Keywords: Coxofemoral Luxation